CHANGES IN TREE SPECIES DIVERSITY OVER TIME IN TROPICAL RAINFORESTS OF CENTRAL REGION, VIETNAM - Thi Thu Hien, Cao (Journal of Forestry Science and Technology, 2016)
To get a better understanding of the tree species diversity in tropical rainforests of Central region, Vietnam, we used a data set from 12 one-hectare permanent sample plots in four provinces. Each plot has a square shape (100 m x 100 m2) and is divided into twenty five 20 m x 20 m quadrats. All trees equal to or larger than 6 cm diameter at breast height (DBH ≥ 6 cm) were identified by species and permanently marked using a white metal tag. Diversity indices and rank type diversity profiles were used to assess and compare the tree species diversity between four locations. The results showed that, the most noticeable trend was a decrease in almost all diversity indices. Tree species diversity varied considerably from province to province. In our study, the conclusion was that intrinsic diversity of plots in Ha Tinh, Thua Thien Hue and Binh Dinh is larger than that of the Khanh Hoa plots. Moreover, the total number of species strictly increased with increasing area, which can be explained by the influence of environmental heterogeneity on the species-area relationship. The species-area curves did not reach their asymptote at the one hectare plot size, which means that one could expect to record new tree species if the sample area would be further increased beyond 10,000 m2.